The Analysis of Inner Mongolian and Mongolian Newspapers’ Linguistic Compositions: The Case of Daily Newspaper - Shuguang (Advances in Social Sciences Research Journal, 2024)
Our study’s objective seems to be to perform a comparative analysis of linguistic compositions from daily newspapers from Mongolia and Inner Mongolia that are written in the Mongolian language. Since linguistic compositions refer to the written content of the newspapers, we looked at and assessed the similarities and differences between linguistic compositions found in newspapers from Inner Mongolia and Mongolia. A few articles, headlines, editorials, ads, and any other textual components found in the newspapers were also examined. Examining the language at various levels, from individual words and phrases to more extensive discourse structures, may be part of our analysis. Daily Newspapers concentrate on daily newspapers, you’re choosing a particular written communication genre that captures the conversation about public policy, social trends, and current events. Historical exchanges between Mongolia and Inner Mongolia as well as political, social, and cultural settings may have an impact on these distinctions. Overall, our research has improved our knowledge of the various contexts and geographical areas in which the Mongolian language is used. It has also illuminated linguistic variances and the influence of socioeconomic and cultural factors on language use. Insights into the dynamic nature of language and its connections to identity, culture, and communication within the Mongolian-speaking community could be gained from it.